Enhancing Class 6 Computer Education with Flash-Based Multimedia at Bukit Islamiah - Hajidorloh, Aneefah; Untari, Rahmania Sri (Universitas Muhammadiyah Sidoarjo, 2024)
This research focuses on developing practical and efficient media for computer systems material aimed at grade 6 students. Employing the ADDIE model, the study progresses through analysis, design, development, and implementation stages to craft a flash-based interactive multimedia. A small-scale trial involving 5 students indicates promising results, with validation scores from media and material experts at 87% and 78%, respectively. Moreover, the average student response stands at 87.2%, affirming the suitability of the developed multimedia for learning purposes. This research underscores the potential of interactive multimedia in enhancing educational experiences, particularly in computer science education for young learners. Highlights : Implementation of ADDIE model ensures systematic development. Flash-based multimedia yields high validation scores from experts. Student response supports suitability for educational use. Keywords: Interactive multimedia, Grade 6 education, Computer systems, ADDIE model, Learning efficiency